Polysaccharide-Based Nanomaterials for Ocular Drug Delivery: A Perspective - Yu, Haozhe; Wu, Wenyu; Lin, Xiang; Feng, Yun (Frontiers in Bioengineering and Biotechnology, 2020)
Ocular drug delivery is one of the most challenging issues in ophthalmology owing to the complex physiological structure of the eye. Polysaccharide-based nanomaterials have been extensively investigated in recent years as an ideal carrier for enhancing the bioavailability of drugs in the ocular system owing to their biocompatibility and drug solubilization. From this perspective, we discuss the structural instability of polysaccharides and its impact on the synthesis process, examine the potential for developing bioactive polysaccharide-based ocular drug nanocarriers, propose four strategies for designing novel drug delivery nanomaterials, and suggest reviewing the behavior of nanomaterials in ocular tissues.